Size effect in shear wave elastography of small solid tumors – A phantom study. (February 2020) - Zhang, Yanfeng; Li, Guo-Yang; Zhou, Jianqiao; Zheng, Yang; Jiang, Yu-Xuan; Liu, Yan-Lin; Zhang, Li-Li; Qian, Lin-Xue; Cao, Yanping
Abstract: Ultrasound shear wave elastography (USWE) enables us to quantitatively characterize the mechanical properties of solid tumors and is of clinical importance in differentiating malignant tumors from benign ones. However, limited by the resolution of USWE, it remains challenging in evaluating the elastic properties of tumors with small dimensions. Here we study the size effect in USWE of tumors via phantom experiments. Gelatin phantoms consisted of spherical inclusions and softer matrix were fabricated to model the tumors embedded in surrounding soft tissues. Our results show that elastic moduli E of the phantom tumors measured with conventional USWE are highly related to their diameters d ( r > 0.96, P < 0.001). The elastic moduli of stiffer phantom tumors were heavily underestimated when the dimension of a tumor is smaller than 1.5 cm, indicating that the size effect should be considered in interpreting USWE of solid tumors. Based on dimension analysis and our phantom experiments, an empirical formula has been proposed to predict the size effect. The method and the results reported here may not only help quantitatively understand the size effect encountered in USWE of solid tumors, but also provide a promising approach to characterize the mechanical properties of soft matter composites in situ .